2018
DOI: 10.1007/s11356-018-1251-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community structure and abundances of antibiotic resistance genes in heavy metals contaminated agricultural soil

Abstract: Soil contamination with heavy metals is a worldwide problem especially in China. The interrelation of soil bacterial community structure, antibiotic resistance genes, and heavy metal contamination in soil is still unclear. Here, seven agricultural areas (G1-G7) with heavy metal contamination were sampled with different distances (741 to 2556 m) to the factory. Denaturing gradient gel electrophoresis (DGGE) and Shannon index were used to analyze bacterial community diversity. Real-time fluorescence quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Significant correlations between ARGs (and intI1 genes) and metal(loid)s in soils reported in previous studies (Cui et al, 2016;He et al, 2014;Ji et al, 2012;Knapp et al, 2017Knapp et al, , 2011Zhang et al, 2018) soil characteristics were positive. One possibility is that bioavailable metal(loid)s in soils were mainly affected by soil characteristics, such as the clay content and SOM (Violante et al, 2010).…”
Section: Tablesupporting
confidence: 49%
See 1 more Smart Citation
“…Significant correlations between ARGs (and intI1 genes) and metal(loid)s in soils reported in previous studies (Cui et al, 2016;He et al, 2014;Ji et al, 2012;Knapp et al, 2017Knapp et al, , 2011Zhang et al, 2018) soil characteristics were positive. One possibility is that bioavailable metal(loid)s in soils were mainly affected by soil characteristics, such as the clay content and SOM (Violante et al, 2010).…”
Section: Tablesupporting
confidence: 49%
“…Indeed, many recent studies have shown significantly positive correlations between ARGs and total metal(loid)s in soils collected from diverse environments, including (Table 3): (1) the relative gene abundance of tetW was correlated with total Cu concentrations in archived soils from the 1940s to the 1970s (Knapp et al, 2011); (2) relative gene abundances of sul1 and sul2 were correlated with total Cu concentrations in Chinese agricultural soils and manure (Cui et al, 2016;Zhang et al, 2018). However, relative gene abundances of tetW demonstrated no significant correlations with total concentrations of Zn, As, Cu in animal manure and agricultural soils.…”
Section: Metal(loid)s In Gsimentioning
confidence: 99%
“…As such, metals can be an even more important risk factor for the proliferation and transmission of ARGs in the environment than other selective agents [ 6 , 7 ]. In the past years, the potential correlations between metal level and ARG abundance or diversity in a variety of environments impacted by agriculture [ 8 ], animal husbandry, aquaculture [ 9 , 10 ], urbanization [ 11 , 12 ] and oil spill [ 13 ] have been studied extensively. However, these focal environments are not exempt from the influences of other selective agents, which has heavily hampered a comprehensive assessment of the direct roles of metals in ARGs proliferation and dissemination in the environment [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…microorganisms by blocking essential functional groups of organic molecules and modifying their active conformations (Li et al, 2017), hence disturbing metabolism and inducing oxidative damage or genotoxicity (Epelde et al, 2015). These disruptions lead to a decrease in the total amount of soil microbial biomass (Ayangbenro and Babalola, 2017) and a reduction in genetic polymorphism in populations (Oleńska and Małek, 2015;Zhang et al, 2018;Oleńska and Małek, 2019). For example, under severe metal exposure where toxic ions compete with essential nutrients like iron, magnesium, phosphorus, calcium, or zinc during root uptake, plant associated bacteria can improve nutrient acquisition by enhancing the nutrient's availability, and as a result increase plant biomass.…”
mentioning
confidence: 99%